1973
DOI: 10.1063/1.1680154
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and circular dichroism spectra of ethylenic chromophores-trans-cyclooctene, α- and β-pinene

Abstract: The absorption and circular dichroism spectra of trans-cyclooctene, α-pinene and β-pinene were measured in the gas phase in the vacuum ultraviolet. The absorptions were recorded to 110 nm and the CD spectra to 150 nm. Consistent assignments were made for these three ethylene chromophore molecules using the measured anisotropy factors (g = Δε/ε) to characterize transitions. Also, available theoretical work was used as a guide. In particular, magnetic dipole allowed transitions in the parent molecule, ethylene, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 13 publications
2
37
0
Order By: Relevance
“…Such low-energy Rydberg excitations from p orbitals to diffuse orbitals are common for chiral bicyclic olefins. [57] However, from experimental CD spectra it has been concluded that b-pinene does not exhibit this low-energy Rydberg transition (both in gas-phase and solution), [58,57] whereas it is indeed predicted in the computations here.…”
mentioning
confidence: 57%
“…Such low-energy Rydberg excitations from p orbitals to diffuse orbitals are common for chiral bicyclic olefins. [57] However, from experimental CD spectra it has been concluded that b-pinene does not exhibit this low-energy Rydberg transition (both in gas-phase and solution), [58,57] whereas it is indeed predicted in the computations here.…”
mentioning
confidence: 57%
“…All gas-phase values in the literature show very good agreement with the g-values of this work. The condensed-phase values in the literature [20][21][22][23][24][25][26][27][28] show similar tendencies, although they differ by a factor of up to three, which is not surprising due to solvent effects. For instance, phenylethanol shows a similar increase in CD in the gas and the condensed phase when changing the wavelength from 266 to 260 nm, as mentioned above.…”
mentioning
confidence: 84%
“…water [17,18] , ethanol [19] (7) S-(À)phenylethylamine 266/-+ 0.65 AE 0.05 phenol + 0.1 water [19] (8) R(À)a-phellandrene 266/-À0.16 AE 0.03 xylene À0.17 gas phase [26] (9) 1(S)5(S)(À)a-pinene 222/-+ 0.38 AE 0.08 xylene + 0.38 gas phase [27] (10) S(À)limonene 213/-À0.16 AE 0.06 xylene À0.13 gas phase [28] [a] Wavelengths of the used one-or two-color REMPI. Table 2.…”
Section: Application Of Enantio-sensitive Rempi To Various Aromatic Mmentioning
confidence: 99%
“…The lowest electronic excitations of alkenes typically occur at substantially longer wavelengths than in the case of alkanes, and their ECD is generally measurable with modern CD instrumentation. While a substantial literature on the ECD of chiral alkenes does exist, ECD has not been widely used in determining the ACs of alkenes, principally because a reliable sector rule, analogous to the octant rule for the n → π * transition of carbonyl groups, has not been available…”
Section: Introductionmentioning
confidence: 99%
“…. These data are compared with the corresponding experimental spectra . Emphasis is given to the predicted ECD spectra dependence with respect to the basis set size and to the used functional.…”
Section: Introductionmentioning
confidence: 99%